Upaya Guru PAI dalam Meningkatkan Kedisiplinan Belajar Peserta Didik melalui Reward dan Punishment di SMPN 1 Nguntoronadi - Habibah Indah Ratnasari; Triono Ali Mustofa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This study aims to analyze the efforts of PAI Teachers in improving students' learning discipline by applying rewards and punishments at SMPN 1 Nguntoronadi. Learning discipline is an important factor that affects the quality of education and academic achievement of students. The use of this research method is descriptive qualitative through a qualitative approach. This research is located at SMP N 1 Nguntoronadi. The data collection techniques were observation, interview and documentation. Interviews were conducted with PAI teachers and the subjects were students in grades VII, VIII, and IX. The technique used to analyze data validity is triangulation. Data analysis used in this research is data reduction, data presentation and conclusion drawing. The results of the research are that PAI teachers at SMPN 1 Nguntoronadi apply various forms of rewards, such as verbal praise, award certificates, and small gifts, to motivate students with disciplined behavior and good learning achievements. Meanwhile, the forms of punishment used include verbal reprimands, additional assignments, and certain sanctions that do not obey the rules or do not show discipline in learning. The application of rewards and punishments has proven effective in optimizing students' learning discipline. They are more motivated to follow the rules and actively participate in the learning process. Teachers also reported an increase in learner engagement and a decrease in the number of discipline violations after the implementation of this measure. However, this study also identified some challenges, such as the need for consistency in the application of rewards and punishments and the importance of a fair and proportional approach. Overall, PAI teachers' efforts through rewards and punishments contributed positively to improving learners' learning discipline at SMPN 1 Nguntoronadi.